2018
DOI: 10.1021/acsami.8b05229
|View full text |Cite
|
Sign up to set email alerts
|

Depletion Mode MOSFET Using La-Doped BaSnO3 as a Channel Material

Abstract: The high room-temperature mobility that can be achieved in BaSnO has created significant excitement for its use as channel material in all-perovskite-based transistor devices such as ferroelectric field effect transistor (FET). Here, we report on the first demonstration of n-type depletion-mode FET using hybrid molecular beam epitaxy grown La-doped BaSnO as a channel material. The devices utilize a heterostructure metal-oxide semiconductor FET (MOSFET) design that includes an epitaxial SrTiO barrier layer capp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…53,75,79,80 n-type BaSnO 3 on SrTiO 3 grown by hybrid molecular beam epitaxy (MBE) has a transmission of ~ 80%. 131 The optical transmission and room-temperature conductivity of BaSnO 3 are comparable to the value of transmission and room-temperature conductivity in ITO. 9,77 Theory predicts BaSnO 3 transmission in the visible range to be independent of doping.…”
Section: Optical and Dielectric Properties Of Basnomentioning
confidence: 74%
See 1 more Smart Citation
“…53,75,79,80 n-type BaSnO 3 on SrTiO 3 grown by hybrid molecular beam epitaxy (MBE) has a transmission of ~ 80%. 131 The optical transmission and room-temperature conductivity of BaSnO 3 are comparable to the value of transmission and room-temperature conductivity in ITO. 9,77 Theory predicts BaSnO 3 transmission in the visible range to be independent of doping.…”
Section: Optical and Dielectric Properties Of Basnomentioning
confidence: 74%
“…Yue et al, however, reported that in devices based on SrTiO 3 (κ = 300) as the gate dielectric, the I on /I off ratio was poor (≈ 2) at room temperature and >10 7 at 77 K. The room-temperature field-effect mobility reported was 70 cm 2 V -1 s -1 compared to 90 cm 2 V -1 s -1 with LaInO 3 as the gate oxides. 126,131 These results also revealed that parameters such as the interface trap density and the band offset between the gate oxide and the channel material play a significant role. Use of a barrier layer of (Sr,Ba)SnO 3 between the gate oxide (parylene) and the BaSnO 3 channel was proposed by Fujiwara et al to suppress the interfacial scattering from traps, which resulted in a mobility of 52 cm 2 V -1 s -1 .…”
mentioning
confidence: 85%
“…The certain value of the volume which is minimum energy of the volume, after this value energy of the volume increases, this is called optimized equilibrium energy, because the system is in the equilibrium. pressure derivatives of the bulk modulus and Bulk modulus at 0 value [21,22,33]. Bulk…”
Section: Optimization Curve Basno3mentioning
confidence: 99%
“…According to the literature, BaSnO 3 (belonging to the perovskite family), shows a wide band gap (E g > 3.1 eV) [ 91 ], a high thermal stability [ 55 ], and a high carrier mobility up to 320 cm 2 ·V −1 ·s −1 in single crystals at room temperature [ 51 ] and 70 cm 2 ·V −1 ·s −1 in epitaxial films [52], respectively. Caused by the high mobility, BaSnO 3 -based materials have been used as a semiconductor layer in oxide thin film transistors (TFTs) [ 92 95 ] and other photoelectronic devices [ 96 – 98 ]. It should be mentioned that the mobility of BaSnO 3 is much higher than that of SrVO 3 .…”
Section: N-type Perovskitesmentioning
confidence: 99%